The Americanized Journey of Chinese Immigrants: The Media Representation of Chinese Immigrants in Disney’s Elemental (2023) - Pascarina, Patrisia Amanda; Hartanto, Louisa Christine; Esther, Jennifer (CHANNEL: Jurnal Komunikasi, 2024)
This paper explores the portrayal of Chinese immigrants in the animated film “Elemental,” using Roland Barthes’ semiotic framework to dissect the film’s narrative and thematic elements. “Elemental” serves as a modern allegory, reflecting the historical and ongoing struggles of Chinese immigrants in the United States, blending elements of cultural identity and adaptation within a fantastical setting. The film juxtaposes the fire element of immigrants with the traditional Chinese immigrant experience, examining themes of cultural integration, systemic discrimination, and the influence of media representation on public perceptions. Through denotative and connotative analyses, the research identifies how the film uses visual and verbal cues to construct a narrative that both challenges and perpetuates long-standing myths and stereotypes about Chinese immigrants. This study not only highlights the specific cinematic portrayal of Chinese immigrants but also discusses broader societal implications, including the impact of “Yellow Peril” propaganda and the role of media in shaping immigration policy discourse. The findings suggest that while “Elemental” contributes to a richer dialogue on cultural diversity, it also reveals the enduring complexities and challenges faced by Chinese immigrants in seeking acceptance and identity in a multicultural society.